Knowledge And Awareness of Autism and Autism Interventions Among the General Public in Chennai - Vishnu Rajkumar, Kaushik; Ganesh. S, Balaji; Jeevitha, M. (Journal of Neonatal Surgery, 2025)
Autism is a developmental disorder characterized by social interaction and communication difficulties with restricted and repetitive behaviour. Early recognition as well as behavioural, educational and family therapies can reduce symptoms, promote learning and development. The aim of the present study was to analyse the knowledge and awareness of autism and autism interventions among the general public in Chennai. A descriptive cross-sectional Survey was conducted among 101 general public in Chennai through a self administered questionnaire. The responses were collected And statistically analysed. 68.3% were aware of the symptoms of autism with p value=0.118>0.05 obtained from the association between the different age groups of the people and awareness of symptoms of autism. 67.3% thought that autism is a genetic disorder with the p value=0.033<0.05 obtained from the association of different age groups of the people and awareness of autism as genetic disorder.This study concluded that the people have good knowledge and Awareness on autism and autism interventions. Diabetes mellitus, particularly type 2 diabetes, is a growing global health issue, often exacerbated by insulin resistance, metabolic disturbances, and inflammatory responses. Emodin, a natural anthraquinone derivative, has been widely recognized for its